(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
Proverbs are an important part of the complex language Tolkien created for Middle-earth: Tolkien as the narrator/author and many of his characters use them. This article discusses Tolkien’s use of proverbs and includes the question of how and why he used proverbs when writing the novel.